匿名使用者
匿名使用者 發問時間: 科學數學 · 1 0 年前

証DY/DX 一題

y= [ (cos x)^m ] ( sin kx)

証dy/dx

= (m+k) [(cos x)^m] (cos kx) - m[(cos x)^(m-1)] [cos (k-1)x]

1 個解答

評分
  • 1 0 年前
    最佳解答

    [ (cos x)^m ] ' = - m * sin x * ( cos x )^ ( m - 1 )

    sin kx = k * cos kx

    dy / dx =

    - m * sin x * ( cos x )^ ( m - 1 ) * sin kx + k * cos kx * [ (cos x)^m ]

    = ( m + k ) * cos kx * [ ( cos x )^m ] - m * cos kx * ( cos x) ^m -

    m * sin x * ( cos x )^ ( m - 1 ) * sin kx

    考慮 m *cos kx *( cos x) ^m + m* sin x *( cos x )^ ( m - 1 ) * sin kx

    => m* ( cos x )^( m - 1 ) * [ cos kx * cos x + sin x * sin kx ]

    = m* ( cos x )^( m - 1 ) * [ cos ( k - 1 ) x ]

    => dy / dx =

    ( m + k )*cos kx *[ ( cos x )^m ]- m*( cos x )^( m - 1 )*[ cos ( k - 1 ) x ]

    2007-10-09 02:14:19 補充:

    第二行

    ( sin kx )' = k * cos kx

    參考資料: myself
還有問題?馬上發問,尋求解答。